Региональная периодическая печать Казахстана в глобальном мире - ШЫНРЫСОВА, Назгул; БАЙМОЛДА, Досан (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
Obecnie w Kazachstanie widać postępujący rozwój mediów regionalnych. Prowadzą one w regionach efektywną pracę informując i kształtując opinię publiczną i świadomość społeczną, w celu zachowania tożsamości społecznej, kulturowej i narodowej. Kazachskie regionalne media zaczęły wykorzystywać mechanizmy rynkowe, takie jak rozwój własnych działań promocyjnych, a także nowe technologie komunikacyjne, jak infolinie, spotkania z czytelnikami, badania oglądalności itp. Kazachscy regionalni redaktorzy łączą uniwersalną publiczność z lokalnymi wiadomościami i wydarzeniami.

Currently, Kazakhstan is focusing on the development of regional media, since it is possible in the regions to conduct effective information work on the formation of public opinion and social consciousness, as well as to preserve social, cultural and national identity. Regional Kazakh media have begun to use market mechanisms, such as their own promotional activities, as well as new communication technologies – telephone hotlines, meetings with readers, audience polls, etc. Kazakh regional editions differ in terms of their integrity, audience, versatility and depth in the coverage of local news and events.
Regional media in Kazakhstan in a globalized world
Media regionalistyczne Kazachstanu w globalnym świecie